PENGARUH METODE INVESTIGASI KELOMPOK TERHADAP KETERAMPILAN BERPIKIR KREATIF SISWA PADA MATERI BENCANA ALAM - Kaffah, Silmy; Panjaitan, Regina Lichteria; Julia, Julia (Jurnal Pena Ilmiah, 2017)
Creative thinking skills direct students to develop ideas and have more than one answer in problem solving. The method of group investigation is a method of learning that requires students to actively ask and express ideas. There is a connection between creative thinking skill and group investigation method, so this research is done to know the influence of group investigation method toward the creative skill of class V student on the material of natural disaster. The research method used is pre-experimental with descriptive one-group pretest-posttest research. The result of research with significance level Î± = 0,05 indicates that learning by using group investigation can improve the creative thinking skill of high, medium and low group student seen from test result of two difference of average pretest and posttets value of each group got result that is 0,000 . While the average difference test results of three moderate high moderate, and low obtained results 0.054. It can be concluded that there is no difference in the improvement of high, medium and low student group thinking skills.